Pengaruh Kepuasan Kerja terhadap Organizational Citizenship Behaviour (OCB) dengan Mediasi Komitmen Organisasional - Anja Raksa Pradhiptya (BISMA (Bisnis dan Manajemen), 2018)
In this era of globalization, competition is so high. An organization will be able to survive, compete and even thrive if an organization's performance continues to operate effectively and efficiently. This study aims to examine and analyze whether job satisfaction to OCB with mediation effect on organizational commitment in PT. Pilih Utama. The population of this research were 52 PT. Pilih Utama employees and use all of the population for sampled. Methods of statistical analysis was used œPartial Least Square (PLS) with the help of SMART PLS software and œStatistical Product and Service Solutions (SPSS) 17.0. This study was found a significant positive effect on job satisfaction to OCB, a significant positive effect on job satisfaction to organizational commitment, a significant positive effect on commitment organizational to OCB, and proves that organizational commitment mediates the effect of job satisfaction to OCB